Effect of grooved cooling passage near the trailing edge region for HP stage gas turbine blade - a numerical investigation. (2017) - Kini, Chandrakant R.; Shenoy, B. Satish; Sharma, N. Yagnesh
Gas turbines have become one of the most important prime movers especially in aircraft propulsion, land-based power generation, and industrial applications. Cooling of gas turbine blades is a major consideration because HP stage blades are subjected to high temperature working conditions. Several methods have been suggested in the past for the cooling of HP stage blades. The main objective of the present work is to study the effect of grooved cooling passages with different geometric shapes for the groove. This method of cooling is specifically useful for cooling the blades near the trailing edge region. In an earlier work by the present authors, optimised helicoidal cooling duct geometry with circular cross-section was proposed and same technique has been incorporated in the present work for augmented cooling of the leading edge region. The analysis is carried out for different types of groove configuration to assess their cooling performance in terms of their cooling efficiency. The major finding of this work is that the cooling duct provided with buttress shaped grooves results in better cooling of the HP stage gas turbine blade.